1/fα power spectrum in the Kardar–Parisi–Zhang universality class. (8th June 2017) - Takeuchi, Kazumasa A
Abstract: The power spectrum of interface fluctuations in the (1  +  1)-dimensional Kardar–Parisi–Zhang (KPZ) universality class is studied both experimentally and numerically. A 1 / f α -type spectrum is found and characterized through a set of 'critical exponents' for the power spectrum. The recently formulated aging Wiener–Khinchin theorem accounts for the observed exponents. Interestingly, the 1 / f α spectrum in the KPZ class turns out to contain information on a universal distribution function characterizing the asymptotic state of the KPZ interfaces, namely the Baik–Rains universal variance. It is indeed observed in the presented data, both experimental and numerical, and in both circular and flat interfaces in the long time limit.